Observational study of the influences of thermal and dynamic boundary layer on the vertical distribution of black carbon aerosol in ShouXian county in wintertime, 2016 - Cheng-gang, Wang; Xia-lu, Wei; Jia-de, Yang; Ting, Ni (Frontiers in Earth Science, 2022)
Using vertical observation data of black carbon aerosol and meteorological parameters in the ShouXian area of Anhui Province from 14 December 2016 to 3 January 2017, the thermal and dynamic effects of the boundary layer on the vertical distribution structure of black carbon were studied. The results show that (1) of 82 vertical sounding profiles obtained during the observation period, there were72 boundary layer sounding profiles dominated by heat and 10 profiles dominated by dynamics. (2) When thermal effects were dominant, the concentration of black carbon aerosol was significantly affected by diurnal changes in the boundary layer. In the unstable boundary layer, black carbon aerosol was uniformly distributed in the vertical direction; during the transition from an unstable to a stable boundary layer, the concentrations of black carbon aerosol were significantly higher in the lower layer than in the upper layer; in the stable boundary layer, the concentrations of black carbon aerosol decreased continuously with height; and during the transition from a stable to an unstable boundary layer, the black carbon aerosol concentrations exhibited high values in the upper layer, with the concentration difference reaching 4 μg·m-3. (3) When the dynamic effect was dominant, the structure of the vertical distribution of black carbon aerosol was affected by wind and by diurnal changes in the boundary layer simultaneously. The high winds (>4 m/s) removed the black carbon aerosol. In the unstable boundary layer, the black carbon aerosol uniformly distributed in the vertical direction had significantly lower concentrations in the high-wind range; when stable boundary layers occurred and during transitions from stable to unstable boundary layers, the black carbon aerosol concentrations were higher in the lower layer and lower in the upper layer. The stratification was more obvious than that observed under thermal control.